Solitary Waves of the Schrödinger Lattice System with Nonlinear Hopping - Ming Cheng (Journal of Function Spaces)
This paper is concerned with the nonlinear Schrödinger lattice with nonlinear hopping. Via variation approach and the Nehari manifold argument, we obtain two types of solution: periodic ground state and localized ground state. Moreover, we consider the convergence of periodic solutions to the solitary waves.